2011
DOI: 10.1093/abbs/gmq121
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells are sensitive to abnormal gravity and exhibit classic apoptotic features

Abstract: The aim of the present study was to investigate the effects of abnormal gravity on human mesenchymal stem cells (hMSCs). Strong magnetic field and magnetic field gradient generate a magnetic force that can add to or subtract from the gravitational force. In this study, this is defined as a high-magneto-gravitational environment (HMGE). The HMGE provides three apparent gravity levels, i.e. hypogravity (mg), hypergravity (2g) and normal gravity with strong magnetic field (1g) conditions. After hMSCs were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…It is widely recognized that several kinds of cells, including endothelial cells, 28 osteoblasts, 29 myoblasts, 30 and stem cells, 31 are sensitive to a change of gravity-force intensity. In particular, it was found that hypergravity treatments could enhance osteogenesis in osteoblast-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that several kinds of cells, including endothelial cells, 28 osteoblasts, 29 myoblasts, 30 and stem cells, 31 are sensitive to a change of gravity-force intensity. In particular, it was found that hypergravity treatments could enhance osteogenesis in osteoblast-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…73 Each system (RPM and RWV) that generates tissue-like cell assembles under microgravity conditions, initially induces an enhanced rate of apoptosis together with an increase in proapoptotic factors. 10,53,60,[74][75][76] In EC, apoptosis seems to impair the angiogenic response to s-mg produced on the RPM. 77 NF-kB1 plays a central role in bone reduction under microgravity conditions.…”
Section: Known Mechanisms Involved In Spheroid Formationmentioning
confidence: 99%
“…The changes in F-actin filaments that occur during weightlessness are in accordance with the disruption of F-actin stress fibers that occur during apoptosis [33]. Disruption of the cytoskeleton and classic apoptotic features have led to the suggestion that MSCs are sensitive to microgravity [20]. Recent studies have demonstrated that simulated microgravity inhibits the osteogenic differentiation of MSCs and osteogenic precursor cells [34,35].…”
Section: The Cytoskeletonmentioning
confidence: 86%
“…A ground-based simulated experimental platform, using the large-gradient superconducting magnet for gravitational biology, has been established ( Fig. 1c) [18,20].…”
Section: Ground-based Platformmentioning
confidence: 99%